Binge-watching addiction as an emotion regulation way of coping loneliness - Xiaofan Yue; Xin Cui (PLoS ONE, 2026)
This study advances understanding of problematic media use by differentiating addictive from non-addictive binge-watching in relation to loneliness—an aspect often overlooked in prior research. It contributes to the field in three key ways: first, by empirically distinguishing problematic from non-problematic binge-watching; second, by demonstrating that loneliness significantly predicts binge-watching addiction but not non-problematic viewing; and third, by identifying escapism and emotional enhancement as dual emotion regulation pathways mediating this relationship, thereby extending existing single-motive frameworks. Using a sample of 551 participants, the study employed correlation and regression analyses to investigate these associations. Binge-watching addiction was assessed using the Problematic Series Watching Scale, and binge-watching motives were measured using the Watching TV Series Motives Questionnaire. Results revealed that loneliness was positively related to binge-watching addiction ( β = 0.325, p < 0.01), but not to non-problematic binge-watching behavior. Analysis identified both escapism ( β = 0.575, p < 0.01) and emotional enhancement motives ( β = 0.429, p < 0.01) as significant factors contributing to binge-watching addiction, suggesting a dual-pathway model of emotion regulation. These findings refine theoretical models of maladaptive media use by illustrating how binge-watching addiction may serve as a behavioral emotion regulation strategy for coping with loneliness via both negative reinforcement and positive enhancement.